2020
DOI: 10.1039/d0tc01464h
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and stable tin-based perovskite solar cell passivated by aminoguanidine hydrochloride

Abstract: Aminoguanidine hydrochloride passivated Sn-perovskite with a power conversion efficiency of 7.3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…S. Abdelaziz et al, numerically modelled and calculated an efficiency of 14.03% from formamidinium tin based perovskite solar cell [17]. Q. Fu et al, fabricated stable tin based perovskite solar cell and obtained an efficiency of 7.3% [18]. Herein, we reports numerical modelling of thin film perovskite solar cells based on Toxic and Non-Toxic material.…”
Section: Introductionmentioning
confidence: 93%
“…S. Abdelaziz et al, numerically modelled and calculated an efficiency of 14.03% from formamidinium tin based perovskite solar cell [17]. Q. Fu et al, fabricated stable tin based perovskite solar cell and obtained an efficiency of 7.3% [18]. Herein, we reports numerical modelling of thin film perovskite solar cells based on Toxic and Non-Toxic material.…”
Section: Introductionmentioning
confidence: 93%
“…The first element considered for lead replacement was tin, which occurs in the same periodic group as lead (G14 element), offering an energy gap of 1.3 eV for MASnI 3Àx Br x . [87,[422][423][424] However, MASnI 3Àx Br x showed extremely low stability (80% performance retention after 12 h in N 2 condition) with an initial PCE of 5.73%. [87] Studies are also reported replacing lead with germanium (Ge, G14 element), resulting in MAGeI 3 with an energy gap of %2.0 eV and PCE of 0.57%, with low stability as well.…”
Section: Monocation B Lead-free Perovskitementioning
confidence: 99%
“…By forming of the strong hydrogen bonding between halide ions in the perovskite by using aminoguanidine hydrochloride (NH 2 GACl) as the coadditive in a perovskite precursor, defects in the perovskite crystals were passivated and energy‐level alignment occurred between the resultant perovskite and the corresponding charge carrier layers. [ 78 ] A successful surface‐controlled growth of FASnI 3 was obtained by introducing 2 mole% pentafluorophen‐oxyethylammonium iodide (FOEI). Highly oriented and smooth FASnI 3 –FOEI perovskite films with a longer charge‐carrier lifetime were fabricated.…”
Section: The Influence Of Lewis Base Additives On Perovskite Solar Pementioning
confidence: 99%